A Theoretical Inquiry into the Ethics of Mathematics Teaching - Paul Ernest (Department of Mathematics Education, 2019)
This paper explores the ethics of the mathematics teacher, starting from the ethical obligations that all human being and professionals share towards those in their care. Most notably this involves a duty of care for students, since teachers can be the most influential persons after their parents. The ethics of mathematics teaching is analysed as concerning the aims of school mathematics, the selection of pedagogy, and the selection of content. The equal treatment of all students is also a central principle, although there are ethical dilemmas posed by the spread of achievement levels in mathematics. The ethical content of school mathematics itself is also considered, although this is a controversial issue. The paper notes that the modern tendency is for teachers to be viewed almost as technicians delivering the centrally decided mathematics curriculum. This paper argues that teachers have ethical agency which can and should still be exercised while meeting professional and institutional obligations.